The design of a five-cell high-current superconducting cavity - 李永明 朱凤 全胜文 Ali Nassiri 刘克新 (Chinese physics C, 2012)
Energy recovery linacs are promising for achieving high average current with superior beam quality.The key component for accelerating such high-current beams is the superconducting radio-frequency cavity.The design of a 1.3 GHz five-cell high-current superconducting cavity has been carried out under cooperation between Peking University and the Argonne National Laboratory.The radio-frequency properties,damping of the higher order modes,multipacting and mechanical features of this cavity have been discussed and the final design is presented.